Kombinasi feses sapi dan babi sebagai sumber biogas - Suriman, D.K.P.; Soputan, J.E.M.; Kalele, J.A.D.; Rawung, V.R.W. (Universitas Sam Ratulangi, 2021)
THE COMBINATION OF COW AND PIG FECES AS BIOGAS SOURCES. This research has been carried out with the aim to find out the biogas production produced from the use of cow and pig feces. This research was conducted at Bailang Abattoir Manado, North Sulawesi. The material used in this study were cow feces, pig feces and water. Comparison of feces combinations (2 bucket cow feces, 1 bucket pig feces and 3 bucket water was 1: 1). The equipment used is a horizontal type digester, measuring, thermometer, pH indicator, biogas stove, hose, barrel and bucket. The data analysis used was in this study was descriptive analysis. The variables observed in this study were biogas volume, temperature, pH value, and biogas application. The 31 days of research showed that the total volume of biogas achieved was 122,266,262 m3. The results also obtained an average temperature of 31ºC for the morning and 30ºC for the afternoon. The pH value of this study 7. The gas test was conducted twice, first on the 15th day. The second test was carried out on day 31. The use of biogas takes 24 minutes to cook. The conclusion of this study is the combination of cow and pig feces with a temperature of 30-31ºC and pH 7 produces 122,266,262 cm3 of biogas with a cooking time of 24 minutes. Keywords: biogas, cow feces, pig feces